2011
DOI: 10.1016/j.expneurol.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the subthalamic nucleus transiently enhances loss-chasing behaviour in patients with Parkinson's Disease

Abstract: a b s t r a c t a r t i c l e i n f oDopaminergic treatments are associated with impulse control disorders such as pathological gambling in a subset of patients with Parkinson's Disease. While deep brain stimulation of the subthalamic nucleus has been reported to reduce symptoms of impulse control disorders in some Parkinson's Disease patients, little is known about its specific effects on gambling behaviour. In this experiment, we investigated the effects of deep brain stimulation of the subthalamic nucleus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 66 publications
0
27
1
Order By: Relevance
“…These dilemmas induce risk-seeking behavior in a variety of social and economic contexts (Kahneman and Tversky, 2000). In addition to showing that activity within the anterior cingulate cortex and subthalamic nucleus mediates loss-chasing choices (Campbell-Meiklejohn et al, 2008;Rogers et al, 2011), we have shown that tryptophan depletion reduces decisions to chase in healthy adults. By contrast, single treatments with 176 mg of the D 2 /D 3 receptor agonist, pramipexole, increase the value of losses that participants are prepared to chase but reduce the value of losses surrendered when deciding to quit gambling (Campbell-Meiklejohn et al, 2011).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…These dilemmas induce risk-seeking behavior in a variety of social and economic contexts (Kahneman and Tversky, 2000). In addition to showing that activity within the anterior cingulate cortex and subthalamic nucleus mediates loss-chasing choices (Campbell-Meiklejohn et al, 2008;Rogers et al, 2011), we have shown that tryptophan depletion reduces decisions to chase in healthy adults. By contrast, single treatments with 176 mg of the D 2 /D 3 receptor agonist, pramipexole, increase the value of losses that participants are prepared to chase but reduce the value of losses surrendered when deciding to quit gambling (Campbell-Meiklejohn et al, 2011).…”
Section: Introductionmentioning
confidence: 71%
“…Administration of the D 2 receptor antagonist, haloperidol, can enhance the reward value of gambling experiences in pathological gamblers (Zack and Poulos, 2007) and alter betting patterns while playing slot machines (Tremblay et al, 2010). Previously, we found that single doses of pramipexole increased the value of losses that human subjects were prepared to chase (CampbellMeiklejohn et al, 2011) while single doses of methylphenidate blocked the tendency of larger losses to suppress chasing behavior (Campbell-Meiklejohn et al, 2012). This suggests that dopamine activity mediate the evaluation of losses in relation to decisions to keep playing during runs of losing outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another investigation (n = 22) evaluated subjects with advanced idiopathic pd and implanted electrodes (subthalamic nucleus) for the purpose of exploring the effect of deep brain stimulation on the inclination to chase losses (Rogers et al, 2011). It concluded that temporary stimulation alters the judgment of collected losses during gambling events in idiopathic pd patients.…”
Section: Overview Of the Experimental Work About The Relationship Betmentioning
confidence: 99%
“…On the other hand, dopamine related treatments like high dosages of anti-Parkinsonian drugs (levodopa, dopamine equivalents, levodopa equivalents; Pontieri et al, 2015), levodopa or dopamine agonists (Weintraub et al, 2010), type B monoamine oxidase inhibitors (Pérez-Lloret et al, 2012), increase the incidence of other impulse control disorders in pd patients based on different studies. On the other hand, deep brain stimulation (sub-thalamic nucleus) in advanced stage pd patients alters the judgment during "chasing losses" (Rogers et al, 2011). 2) The incidence of gambling disorder in pd patients can be partially explained by aging effects on cognitive processes, based on the works of Isella et al (2008) and Zamarian et al (2008).…”
Section: Conclusion Of the Experimental Work About The Association Bmentioning
confidence: 99%